Nilai Sosial Budaya dalam Novel Jenderal Kambing Karya Khrisna Pabichara (Perspektif Kajian Sosiologi Sastra) - Sorraya, Artifa; Zahrotul Lutfiyah, Luly (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
This research is entitled "Socio-cultural Value in General Kambing Novel by Khrisna Pabichara Perspective of Sociology of Literature". The interesting thing about General Kambing's novel is the structure of the novel, and the socio-cultural life contained in the novel. So that this research only focuses on the structure of the novel and what socio-cultural values ​​contained in the novel Gen Kambing. The subject of this study was the novel Gen Kambing by Khrisna Pabichara. The object of this research is the whole data that relates to the existing socio-cultural values, so that the whole part of the novel is considered to support the research data. In accordance with the type of research, data analysis was carried out using descriptive qualitative methods to analyze this novel. In its application, heuristic and hermeneutic reading methods are used. Heuristic reading method is a way of working done by readers by interpreting structurally. While the method of reading hermeneutics is to find meaning. This method is a way of working done by the reader by reading back and forth from beginning to end.